2016
DOI: 10.1016/j.ejmech.2016.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the non-amyloid-component (NAC) domain and the KTK(E/Q)GV repeats stabilize the α-synuclein fibrils

Abstract: The aggregates of α-synuclein (αS) are a major pathological hallmark of Parkinson’s disease (PD) making their structure-function relationship important for rational drug design. Yet, the atomic structure of the αS aggregates is unavailable, making it difficult to understand the underlying aggregation mechanism. In this work, based on available experimental data, we examined plausible molecular structures of αS(20/30–110) fibrils for the first time by employing computational approaches. The optimized structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 65 publications
3
34
0
1
Order By: Relevance
“… 12 Initial constructed models of self-assembled AS(30–95) octamers. Model C1 is an ssNMR structure observed by Rienstra group, 15 model C2 is predicted from the computational study of Xu et al, 13 and model C3 is predicted in this study.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“… 12 Initial constructed models of self-assembled AS(30–95) octamers. Model C1 is an ssNMR structure observed by Rienstra group, 15 model C2 is predicted from the computational study of Xu et al, 13 and model C3 is predicted in this study.…”
Section: Introductionsupporting
confidence: 55%
“…We further examined the self-assembled structures of AS(30–95) based on the fivefold model that consists of residues 30–110. 13 In C2 model ( Figure 1 ), the residues 96–110 in the original fivefold model were removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the average RMSD values in the three MD runs of the isolated tetramer system during 250-300 ns were respectively 0.34, 0.32, and 0.32 nm; with the addition of DA/NE, the values changed to 0.35, 0.69, and 0.41 nm. Previous computational studies also reported that αS 20/30-110 pentamer [70], αS 61-95 pentamer [71], and αS 29-98 decamer [72] could maintain the β-sheet structures and display a stable conformation during the MD simulations. The increased RMSD value of αS tetramers with DA/NE molecules compared to those without DA/NE molecules suggested that the binding of DA/NE molecules led to a decreased structural stability of αS tetramer.…”
Section: Discussionmentioning
confidence: 81%
“…It can also adopt a partial helical structure in the presence of a membrane [25, 26]. The mechanism by which αS self-associates has been extensively investigated [2737], yet effective therapeutic strategies that inhibit αS aggregation processes and prevent the progression of Parkinson’s disease do not exist to date. However, several small molecules that interact with αS and alter the aggregation process, including phthalocyanine tetrasulfonates [38], epigallocatechin gallate [39], N-(4-Fluorophenyl)benzenesulfonamide [40], curcumin [41], CLR01 [42], gallic acid [43], and nortriptyline [44] have been identified.…”
Section: Introductionmentioning
confidence: 99%